MODEL PROGRAM DAN PELAKSANAAN PERKULIAHAN MKU BAHASA INDONESIA (Studi Deskriptif-Analitis terhadap Program dan Pelaksanaan Perkuliaham MKU Bahasa Indonesia di Fakultas Sain dan Teknologi UIN Sunan Gunung Djati Bandung) - Yeti Heryati (JURNAL ISTEK, 2015)
The research is based on several studies that show the weakness of student language skills, especially on writing skills. Such skills can be maximized through learning MKU Bahasa. Therefore, this problems of research is how the program picture is and how to execute the lecturing of MKU Bahasa in the Faculty of Science and Technology of UIN Sunan Gunung Djati Bandung which are able to enhance the student language skills. The data of this research is the syllabus and lecturing SAPand the execution of lecturing of MKU Bahasa. The tecnique in collectingdata done by the way of documentation study, observation, and quastionnaire. The result of documentation study suggest that syllabus of MKU Bahasa have loaded most materials for scientific writing. In the case of lecturing implementation, there are three main activity namely intriduction, the content and the conclusion. From amount of lecturing sissions, the portion practice is larger for writing compared to the theory.